Induction of defence response in lignin biosynthesis of Elaeis guineensis during an interaction with Ganoderma boninense - Goh, Kar Mun (2016)
Oil palm is a dynamic economic crop that provides good income and is a source of dietary energy for the global population by palm oil. However, oil palm has low resistance to basal stem rot (BSR) disease caused by Ganoderma boninense. It is hypothesised that the process of cell wall lignification could serve as the first line of defence in oil palm. Lignification delays the infection progress of G. boninense. This present study evaluated the underlying molecular and biochemical lignin biosynthesis events and the quantification and deposition patterns of lignin in oil palm upon G. boninense infection. In this study, an artificial in planta infection system was used to inoculate one month-old oil palm plantlets with G. boninense (GBLS strain) at three levels of treatments (control, T1; wounded, T2 and infected, T3). Post-infection analyses were conducted at 2 day intervals for a period of 8 days. The analyses included the disease severity index (DSI) and physical properties of the plantlets (height, weight, stem diameter, root length and leaf chlorophyll content), the degree of G. boninense colonisation on plantlets stem tissues, total phenolic content and total amount of G. boninense DNA in planta. The results showed a significant (P < 0.001) reduction in the leaf chlorophyll content (from 32.59 to 12.61 SPAD) and severe deterioration of the internal stem tissues. Escalation of DSI values (from 5.56 to 70.37%), total phenolic contents (from 1.78 to 3.07 mg g-1) and the quantity of G. boninense DNA (from 4.04 to 757.15 mg g-1) in the infected (T3) plantlets on 8 day post-inoculation (DPI) were observed. These differences (P > 0.05) were absent in control (T1) and wounded (T2) plantlets. Colorimetric enzyme assays and quantitative PCR amplifications (qPCR) were carried out to assess the enzyme activities and relative gene expressions of intermediate enzymes (phenylalanine ammonia lyase, PAL; cinnamate 4-hydroxylase, C4H; caffeic acid O-methyltransferase, COMT; cinnamyl alcohol dehydrogenase, CAD) for lignin biosynthesis in oil palm plantlets. Enzyme activities of PAL, C4H and COMT were generally induced in infected plantlets, except for CAD which was reduced in all plantlets throughout the experiment. Meanwhile, relative expression of EgPAL, EgCOMT and EgCAD were up-regulated in infected plantlets by 3 to 6 fold at 2 to 4 DPI as compared to the control plantlets, except for EgC4H which was initially down-regulated, but was induced later at 8 DPI with the highest change recorded of 13.22. A biphasic transient induction pattern of lignin biosynthesis genes was observed in oil palm plantlets upon infection by G. boninense. The lignothioglycolic acid (LTGA) assay, histochemical staining with toluidine blue-O (TBO), Maúle reagent and phloroglucinol-HCl and gas chromatography (GC) equipped with a flame ionisation detector (FID) were used to estimate and detect the total lignin content, lignin deposition patterns and the composition of lignin derivatives such as syringaldehyde and vanillin, respectively. Results showed the infected plantlets scored the highest level of total lignin content at 93.63 TGA g-1 derivatives at 8 DPI. Lignin was mainly deposited on the collenchyma and cuticle layers, as observed via staining with TBO and Maúle reagents, but red colouration from phloroglucinol-HCl, which stained for guaiacyl-lignin was absent in all specimens. Total amounts of syringaldehyde and vanillin increased in infected plantlets at 6 DPI, with higher increment of vanillin (353%) than syringaldehyde (59%) content. From this study, an early induction of lignification in oil palm was confirmed in response to the infection of G. boninense. This resulted in the accumulation and deposition of lignin compounds in the cell walls of oil palm. An increase in lignin content of oil palm was believed to have enhanced its tolerance towards G. boninense infection and delayed the progression of BSR disease, which could be a temporary solution to the BSR problem in oil palm. Further research for an effective cure or prevention is required.